2022
DOI: 10.1097/md.0000000000028992
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes after elective double-embryo transfer in frozen cycles for women of advanced maternal age

Abstract: We aimed to determine the clinical outcome of double cleavage-stage embryo transfers in frozen-thawed embryo transfer cycles for older women.This study analyzed a total of 8189 cleavage-stage frozen-thawed embryo transfer cycles between January 2013 and December 2017 at Sir Run Run Shaw Hospital. All cycles were sorted into 3 groups based on patient age: 35 years (Group A), 36 to 37 years (Group B), and ≥38 years (Group C). The clinical pregnancy rate (CPR), implantation rate (IR), live birth rate (LBR), misca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
(42 reference statements)
1
4
0
Order By: Relevance
“…Patients 35 years and older had only a small benefit from the transfer of a second poor-quality blastocyst-stage embryo, as there was no obvious increase in the LBR, whereas the MBR increased by 8.3%. These findings are in line with previous data showing the benefit of SET in patients younger than 35 years [ 13 , 28 ]. Interestingly, the study by Wang et al [ 14 ] showed that in patients aged < 35 years, the multiple pregnancy rate (MPR) was significantly greater in the GQE + PQE group than in the single GQE group, with no significant differences in the LBR.…”
Section: Discussionsupporting
confidence: 93%
“…Patients 35 years and older had only a small benefit from the transfer of a second poor-quality blastocyst-stage embryo, as there was no obvious increase in the LBR, whereas the MBR increased by 8.3%. These findings are in line with previous data showing the benefit of SET in patients younger than 35 years [ 13 , 28 ]. Interestingly, the study by Wang et al [ 14 ] showed that in patients aged < 35 years, the multiple pregnancy rate (MPR) was significantly greater in the GQE + PQE group than in the single GQE group, with no significant differences in the LBR.…”
Section: Discussionsupporting
confidence: 93%
“…The incidence of heterotopic pregnancy is overall rare but it increases with increased number of embryos transferred during a single IVF cycle. 5,6 Decision for multiple embryo transfer is frequently influenced by maternal age as advanced maternal age is associated with lower pregnancy and live birth rates. 5 Other factors that may influence number of embryos transferred include history of past IVF outcomes, financial considerations, embryo quality, and patient preference.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Decision for multiple embryo transfer is frequently influenced by maternal age as advanced maternal age is associated with lower pregnancy and live birth rates. 5 Other factors that may influence number of embryos transferred include history of past IVF outcomes, financial considerations, embryo quality, and patient preference. 5,7 To reduce the risks associated with multiple gestation pregnancies the American Society for Reproductive Medicine (ASMR, formerly The American Fertility Society) recommends limiting the number of embryos transferred during a single cycle with an aim to promote transfer of a single gestation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated that, the characteristics of the treated couple and FET cycle parameters were associated with preterm birth and low birth weight in the FET cycles. 15 , 16 However, some studies have found no association between FET with preterm birth and low birth weight. 17 In general, there are still inconsistent results on the relationship between different indicators of FET and fetal preterm birth and low weight at home and abroad.…”
Section: Introductionmentioning
confidence: 99%